Brazilian Goldmines in its first edition - Leni Ribeiro Leite (Classica, Revista Brasileira de Estudos Clássicos)
This is a review of the recent publication of As Minas de Ouro do Brasil. Brasilienses Aurifodinae, with translation by Alexandra de Brito Mariano.